Haida whale totem in front of government building, Wrangell, Alaska, ca. 1913 - Thwaites, John E.
Whale grave totem, Alaska, ca. 1906-1922. Set on display in lawn next to wooden building. Noted from unidentified sources: Grave marker of whale on post in front of government building, Wrangell.